Experimental investigations on flexural behavior of RC beams strengthened with CFRP, GFRP and hybrid FRP wrapping under static load - Shanmugam, U.; Manoharan, P. Devadas; Neelamegam, M. (Journal of Structural Engineering, 2024)
An experimental investigation was conducted on reinforced concrete beams under static load in flexure for studying the behavior in service and ultimate load conditions. The beams were wrapped with carbon fibre reinforced polymer (CFRP), glass fibre reinforced polymer (GFRP) and hybrid (Alternative layers of CFRP and GFRP) composites in un damaged condition. The wrapping was also carried out for the beams loaded up to service load and ultimate load. Ductility behaviors viz., deflection ductility, energy ductility and curvature ductility of all the beams are presented in this paper. Beams strengthened with CFRP and GFRP registered enormous increase in load carrying capacity in first crack, yield and ultimate stages when compared to control beam. The percentage increase in service load of control beams with CFRP, GFRP and hybrid (CFRP + GFRP) are found to be about 41% to 51%. The ultimate load was observed to be about 67% to 110%. The repaired beams with CFRP, GFRP and hybrid (CFRP + GFRP) loaded up to service load was observed to be 25% to 52% and 87% to 123% for ultimate load. Compared to control beam, the reduction in strain values at compression and tension zones at first cracking load levels in strengthened beams are in the range of 36% to 94% and 23% to 83%, respectively. The strains at yield and ultimate load levels are also significantly reduced in strengthened beams. Results clearly showed that both flexural strength and stiffness of reinforced concrete beams were increased and it will be more effective if the structural members retrofitted or rehabilitated by CFRP, GFRP and combination of the both in bonding technique.